Lying about money and game points by men and women and its relation to the Self-Reported Lying Scale - Elaad, Eitan; Kochav, Ron; Elkouby, Tamar (Frontiers in Psychology, 2024)
The present study examined the effect of monetary and non-monetary endowment on lying by men and women in the Ultimatum Game. Examinees (162, 82 women) were allocated to four experimental conditions in a 2 x 2 factorial design. Two endowment conditions (money and game points) were crossed with two sex conditions (men and women). The results indicated that more cash than points were concealed from an unidentified partner, and men concealed more of the endowment than women. We further defined fake fairness in sharing that combined hiding a more significant portion of the endowment from the partner while presenting fair sharing of the remaining award. We found more fake fairness when money was shared than when points were concealed. Fake fairness is more significant for men than for women. For money and points alike, concealment was predicted by the global score of the Self-Reported Lying Scale (SRLS) and by most of its five subscales (self-assessed lying ability, self-assessed lie detection ability, the use of reason in lying, lying acceptability, and lie frequency). The SRLS is described here for the first time, and its potential use is discussed.